Novel platform leveraging electronic medical record (EMR) to triage patients admitted with high-grade immune-related adverse events (irAEs) to the immune-toxicity (ITOX) service. Issue 2 (18th August 2020) - Abu-Shawer, Osama; Singh, Prabhsimranjot; Yenulevich, Eric; Brito, Amanda; Ni, Jian; Abdulnour, Raja-Elie E; Grover, Shilpa; Manos, Michael; Bowling, Peter; LeBoeuf, Nicole R; Ott, Patrick; Stephen Hodi, F; et al.
Abstract : Background: The incidence of high-grade immune-related adverse events (irAEs) due to immune checkpoint inhibitors (ICIs) is increasing due to the rapid expansion of indications for their use. There is an urgent need for a feasible approach of identifying patients with high-grade irAEs to ensure early detection and proper management of this unique set of toxicities. Methods: We established one of the first inpatient services that are specifically devoted to mitigating irAEs. The service uses a multidisciplinary approach with consulting service from experts in managing irAEs. We are leveraging the electronic medical record (EMR) to triage patients who are admitted to the hospital and have received or are currently receiving ICIs. A list of patients with ICI exposure is generated daily by EMR and then curated manually to identify patients with potential irAEs. Results: A total of 129 patients with high-grade irAEs were admitted between June 2018 and June 2019. The most common irAEs were colitis (32%), pneumonitis (30%), and hepatitis (14%). Eighty five per cent of the patients had grade 3 irAEs and 15% had grade 4–5. About half of the patients had received ICI monotherapy; 30% had received combination of ICIs and non-ICIs; and 19% had received a combination of ICIs. Only 9% of patients had steroid-refractory irAEs requiring other immunosuppressive agents. The average length of stay for irAE-related admission was 11 days with a readmission rate due to recurrent irAEs of 26% within a year. Conclusion: We demonstrated the feasibility of using the EMR to accurately triage patients with suspected irAEs to a dedicated immune-toxicity service. Our model is adaptable in major academic centers and could have a major impact on quality of care and future clinical research addressing irAEs.